Process Safety Index in Chemical Process - Dyan H.A Sudarni; Juwari Juwari (Institut Teknologi Sepuluh Nopember, 2017)
Safety is a strategy to reduce the risk of major process accidents. The principle of a safety is to reduce the risk of fails and can be applied easily as the inherent safety. the research which assesses the safety and appeared have a lot of new methods. This study tried to summarize some of the existing methods. The study focused on the case of making methyl methacrylate (MMA) with acetone cyanohydrin (ACH). The processing manufacturing production is divided into four stages or routes. Which are production of hydrogen cyanide (HCN), acetone cyanohydrin (ACH), HMPSA/HMPSE and methyl methacrylate (MMA). Safety assessment is a stages with standardization. Standardization aims to ease look at the risk level of a route. Assessment standardization it produces characteristic safety assessment of the risk level. The level of these characteristics assess any level of danger when the process conditions of a factory. Each production process of the plant there are several production steps. The steps in the production process including preparation, reaction, separation and purification. Of these processes often occur a failure. Then table the characteristics of this suggested to simplify petrified assess how the level of security in the process. In research took a case of making MMA with ACH. The process of making this MMA has four step process HCN, ACH, HMPSA / HMPSE and MMA. The four steps greatest potential failure or hazard is found in the first step with the characteristic 'Moderate', the according to the characteristics of the proposed table.